Prevalence of risk factors for chronic kidney disease among civil servants in Kano - Nalado, Aisha; Abdu, Aliyu; Muhammad, Hamza; Abdu, Alhaji; Sakajiki, Aminu; Adamu, Bappa; Adamu, Bappa (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Data on the epidemiology of chronic kidney disease (CKD) from sub-Saharan Africa are still sparse. Preventive strategy through early detection and treatment has been advocated for CKD, especially in our environment where majority of patients present late and cannot afford the cost of renal replacement therapy which is not widely available. We investigated the prevalence of risk factors for CKD among the civil servants who volunteered after a public enlightenment campaign in Kano, northern Nigeria. Materials and Methods: We studied 225 apparently healthy civil servants who availed themselves of the opportunity to be screened for risk factors for CKD during the 2011 World Kidney Day activities. Relevant demographic and clinical data were obtained using a questionnaire. Weight, height, Body Mass Index (BMI), and blood pressure were measured. Spot urine samples were collected and tested for protein, sugar, and other parameters using a dipstick. Random blood sugar was measured with a glucometer. Results: The mean age of the study participants was 41.5 ± 9.68 years. Males constituted 83.6% of the respondents. Majority had a positive history of use of traditional medications, followed by the use of analgesic drugs, while very few (less than 5% each) admitted to alcohol ingestion or use of bleaching creams. While there was a significant family history of hypertension and diabetes, only about 3% had positive family history of kidney disease. Proteinuria was found to be present in 19.4%. Other risk factors found include hypertension (29.8%), obesity (11%), and diabetes mellitus (3.6%). Conclusion: Risk factors for CKD are common among civil servants in Kano. The most frequent CKD risk factors found among the study subjects were use of traditional medication, cigarette smoking, obesity, hypertension, and proteinuria.